2013
DOI: 10.1002/jsfa.6374
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and biochemical characterization of transgenic papaya modified for protection against Papaya ringspot virus

Abstract: The findings suggest that transformation did not produce any major unintended alterations in the physicochemical attributes of the transgenic papayas. Transgene proteins in the edible fruit pulp were low or undetectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…All fatty acids were expressed as percentage with respect to the total fatty acids (Table ). Among them, consistent with previous results, palmitic acid (C16:0), oleic acid (C18:1), and linoleic acid (C18:3) were the most abundant fatty acids of transgenic virus-resistant soybeans and their nontransgenic counterpart. The percentage values of the majority of the measured fatty acids fell within the ranges of the ILSI database, except palmitoleic and heptadecenoic; the contents of these two fatty acids were lower than the minimum values.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All fatty acids were expressed as percentage with respect to the total fatty acids (Table ). Among them, consistent with previous results, palmitic acid (C16:0), oleic acid (C18:1), and linoleic acid (C18:3) were the most abundant fatty acids of transgenic virus-resistant soybeans and their nontransgenic counterpart. The percentage values of the majority of the measured fatty acids fell within the ranges of the ILSI database, except palmitoleic and heptadecenoic; the contents of these two fatty acids were lower than the minimum values.…”
Section: Results and Discussionsupporting
confidence: 92%
“…The present study was designed to evaluate the composition of the RNAi-mediated virus-resistant transgenic soybeans engineered with hairpin construct and their nontransgenic counterpart through a series of chemical analyses to determine whether significant undesirable biologically changes occurred by the IR insertion in transgenic soybeans, using the concept of “substantial equivalence”, which was developed by the Organisation for Economic Co-operation and Development (OECD) in 1993 and was elaborated further by FAO/WHO. , The concept suggests that if no meaningful difference from the conventional counterpart is found, then the transgenic crop is as safe and nutritious as its traditional counterpart, which is generally accepted as safe on the basis of human food use history. Substantial equivalent analysis has been studied for different events of transgenic crops, such as corn, , soybean, rice, and papaya …”
Section: Introductionmentioning
confidence: 99%
“…In the analyzed studies, associations between ethnicity and socioeconomic variables showed no agreement. 15 - 17 , 19 , 22 , 25 One of the explanations, according to Roberts et al, 17 would be that sleep problems are associated with the social status of a minority, not being associated with ethnicity. Another important point, according to some authors, 16 , 17 is the fact that young individuals who belong to minority groups can express mental suffering in a negative way, especially among immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Nos estudos analisados, as relações entre etnias e as variáveis socioeconômicas não entraram em consonância. 15 - 17 , 19 , 22 , 25 Uma das explicações, segundo Roberts et al., 17 seria que os problemas do sono estariam relacionados à condição social de minoria, e não à origem étnica. Outro ponto a ser destacado, segundo alguns autores, 16 , 17 é o fato de jovens pertencentes ao grupo das minorias poderem expressar de forma negativa o sofrimento psíquico, especialmente entre os imigrantes.…”
Section: Discussionunclassified